Organic Concept in Rolf-Dieter Arens’s Piano Teaching Strategy - Yonathan, Aylwin (Malaysian Journal of Music, 2022)
Rolf-Dieter Arens is a distinguished and revered musical figure with a career spanning more than fifty years as a concert pianist, chamber musician, and educator. His innovative teachings have influenced professional pianists, teachers, and students worldwide. The purpose of this study is to document and explain Arens’s distinct piano teaching approach. Data collection methods were participant observation, interviews with students and communication with Arens. Arens’ teaching strategies involve ideas such as the establishment of goals, modelling, listening, visualisation, deconstruction of the musical structure, and subdivision support. However, a major distinction in Arens’s teaching as compared to others is the notion that techniques and artistic interpretation are a holistic unit and are taught simultaneously rather than compartmentally is common. Another major aspect of Arens’s teaching approach involves what is called the “organic” flow which is an understanding of how the musical structure should regulate the artistic and technical decisions for performance. This study provides a substantial guide and reference to pianists and pedagogues who wish to expand their perspectives in the process of music-making as well as improve their teaching and performance techniques.